Evaluation of Endothelial Function in Pre-Menopausal Women with Coronary Arterial Disease - Farias,Wilma Karlla dos Santos (2017)
Abstract Background: The endothelium plays an important vascular regulatory function. Its dysfunction is an early marker of cardiovascular risk. However, there are few studies in our community that assess endothelial function in pre-menopausal women. Objective: To assess endothelial function in pre-menopausal women in the presence or absence of coronary artery disease, using a biophysical method (carotid intima media thickness) and a biochemical method (serum levels of hsCRP). Methods: Cross-sectional study that evaluated carotid intima-media thickness and serum levels of hsCRP of 31 pre-menopausal women undergoing coronary angiography at the Hemodynamics Service of Hospital Universitário da Universidade Federal do Maranhão from March 2012 to July 2013. The data were sent to statistical analysis and a statistical significance level of 5% was considered. Results: The sample was divided into two groups according to the presence of coronary artery disease (CAD): CAD group (n = 13) and group without CAD (n = 18). The average ages for the groups were 57.92 ± 5.17 and 51.72 ± 4.63 years, respectively (p = 0.001). CIMT was abnormal in 29.03% in the general population. Carotid intima-media thickness was 1.55 ± 0.78 mm in the general group, 1.92 ± 0.94 mm in the CAD group and 1.18 ± 0.71 mm in the group without CAD (p = 0.001). CAD patients had predominance of abnormal CMIT compared those without CAD: 36.46% vs. 22.22%, respectively. There was a sensitivity of 38%, specificity of 77% with a positive predictive value of 0.55 and a negative predictive value of 0.63 with likelihood ratio of 1.73. Patients with abnormal CIMT presented higher levels of hsCRP, but without statistical significance. CAD patients had higher levels of hsCRP, but without statistical significance. Conclusion: In the population studied, assessment of endothelial function using the CIMT method showed higher sensitivity and specificity for the diagnosis of CAD compared to the measurement of hsCRP levels in menopausal women.